Molecular simulation aided nanoporous carbon design for highly efficient low-concentrated formaldehyde capture. (November 2017) - Kowalczyk, Piotr; Miyawaki, Jin; Azuma, Yuki; Yoon, Seong-Ho; Nakabayashi, Koji; Gauden, Piotr A.; Furmaniak, Sylwester; Terzyk, Artur P.; Wisniewski, Marek; Włoch, Jerzy; Kaneko, Katsumi; Neimark, Alexander V.
Abstract: Although recent experimental studies have demonstrated that doping of nanoporous carbons with nitrogen is an effective strategy for highly diluted formaldehyde capture, the impact of carbon surface chemistry and the pore size on formaldehyde capture at ∼ppm concentrations is still poorly understood and controversial. This work presents a combined theoretical and experimental study on dynamic formaldehyde adsorption on pure and oxidized nanocarbons. We find using Monte Carlo simulations and confirm experimentally that cooperative effects of pore size and oxygen surface chemistry have profound impacts on the breakthrough time of formaldehyde. Molecular modeling of formaldehyde adsorption on pure and oxidized model nanoporous carbons at ∼ppm pressures reveals that high adsorption of formaldehyde ppm concentrations in narrow ultramicropores <6 Å decorated with phenolic and carboxylic groups is correlated with long formaldehyde breakthrough times measured in the columns packed with specially prepared oxidized activated carbon fiber adsorbents with the pore size of ∼5 Å. Graphical abstract: